2011
DOI: 10.1016/j.carres.2011.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Caenorhabditis elegans proteins captured by immobilized Galβ1-4Fuc disaccharide units: assignment of 3 annexins

Abstract: Abbreviations: ACN, acetonitrile; EDTA, ethylenediaminetetraacetic acid; LC-MS/MS, liquid chromatography-tandem mass spectrometry; TFA, trifluoroacetic acid Pre-print version Takeuchi T. et al. Carbohydrate Research 346 (2011) Adsorbed C. elegans proteins were eluted with ethylenediaminetetraacetic acid (EDTA) and followed by lactose (Galβ1-4Glc), digested with trypsin, and were then subjected to proteomic analysis using LC-MS/MS. Three annexins, namely NEX-1, -2, and -3, were assigned in the EDTA-eluted f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…It is reported that NPY may be involved in the abnormal electrical activity in the vulnerable hippocampus neurons during epileptic seizure [38], and its levels increase in different types of epilepsy [39]. GAL is also widely distributed in the central and peripheral nervous systems and acts through G protein-coupled receptor that play an important role in the control of seizures in animal epilepsy [10] [40]. In this study, we showed that levetiracetam markedly lowered NPY and GAL levels in plasma and CSF in patients with refractory epilepsy (P \ 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that NPY may be involved in the abnormal electrical activity in the vulnerable hippocampus neurons during epileptic seizure [38], and its levels increase in different types of epilepsy [39]. GAL is also widely distributed in the central and peripheral nervous systems and acts through G protein-coupled receptor that play an important role in the control of seizures in animal epilepsy [10] [40]. In this study, we showed that levetiracetam markedly lowered NPY and GAL levels in plasma and CSF in patients with refractory epilepsy (P \ 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…They also provide an eight carbon spacer arm. In carbohydrate affinity chromatography, the method is appropriate for coupling glycoproteins and carbohydrates or, more often, carbohydrate derivatives containing an amino group (Takeuchi et al, 2011).…”
Section: The N-hydroxysuccinimide Methodsmentioning
confidence: 99%
“…A spacer group can be attached to the carrier (Section 4.2), or alternatively, sugar derivatives can be synthesized by attaching spacers, such as 6-amino-hexyl and ε-aminocaproyl groups (Lis & Sharon, 1981). Several carbohydrate derivatives have recently been synthesized and utilized in affinity chromatography for lectin isolations, such as the Galǐ1-4Fuc derivative containing a hydrophilic spacer modified with a free amino group (Takeuchi et al, 2011), an iodoacetamidyl derivative of Glc 1 Man 9 GlcNAc 2 (Watanabe et al, 2007), and a derivative of L-fucose with a BSA spacer (Argayosa & Lee, 2009). In addition, a novel method for covalent immobilization of a range of carbohydrate derivatives onto polymeric resin beads has been described .…”
Section: Mono-and Disaccharidesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as evidenced by site-directed mutagenesis, each of the eight amino acid residues in LEC-6 had a relatively small impact on the interaction with Galb1-4Fuc compared to that with Galb1-4GlcNAc [16]. Furthermore, experiments with immobilized-Galb1-4Fuc have revealed that various C. elegans galectins have the affinity for Galb1-4Fuc disaccharide [20], although the eight amino acids are relatively less conserved in C. elegans galectins [21], for example, LEC-9, which has two substitutions among the 8 amino acid residues, could bind immobilized-Galb1-4Fuc. These results indicate that immobilized Galb1-4Fuc adsorbent may be useful for affinity purification of mutant galectins that cannot bind vertebrate-type glycans.…”
Section: Introductionmentioning
confidence: 96%